G79(P) Physician and parental decision-making prior to acute medical admission. (12th March 2018) - Barwisemunro, R; Morgan, H; Turner, S
Abstract : Background: There is a rising number of acute medical paediatric emergency hospital admissions in England and Scotland, and the rise is explained by increased short-stay admissions. Our objective was to undertake qualitative interviews with parents and clinicians to better understand what factors, other than the health status of the child, may influence decision-making leading to an admission. Methods: Semi-structured interviews were conducted with parents, clinicians working in general practice, out-of-hours or accident and emergency (referring clinicians) and doctors working in acute medical paediatrics (receiving clinicians) within 24 hours of a child being admitted to hospital Results: Ten parents (including one caregiver), seven referring clinicians and ten receiving clinicians were interviewed. Parents described erring on the side of caution when seeking medical opinion and one mentioned anxiety. Among themes seen among referring clinicians, 'erring on the side of caution' was also identified as was managing 'parental anxiety' and acting on 'gut instinct'. Among receiving clinicians, themes included managing parental anxiety and increasing parental expectations of the health service. Conclusions: The study of parent and referring clinician decision-making prior to a hospital admission can identify 'teachable moments' where interventions might be delivered to slow or even arrest the rise in short-stay acute medical admissions. Interventions might, for example, assure parents or referring clinicians that hospital referral is not required and help clinicians understand what they interpret as 'parental anxiety'.